Dietary diversity of the vulnerable leaf-eating monkey Presbytis fredericae in the degraded forest of Mount Merbabu, Indonesia - PUGUH KARYANTO; DHINDA TAZKIA; IKE NURJUITA NAYASILANA; ARI SUSILOWATI; SUNARTO SUNARTO; JAROT WAHYUDI; SRI SUTJI UTAMI ATMOKO; SHUKOR MD NOR (Society for Indonesian Biodiversity, 2025)
Abstract. Karyanto P, Tazkia D, Nayasilana IN, Susilowati A, Sunarto, Wahyudi J, Atmoko SSU, Nor SM. 2025. Dietary diversity of the vulnerable leaf-eating monkey Presbytis fredericae in the degraded forest of Mount Merbabu, Indonesia. Biodiversitas 26: 2508-2518. Extensive forest degradation and fragmentation on Java Island, Indonesia, have resulted in significant habitat loss and a sharp decline in tree diversity. The remnant forests, characterized by declining plant diversity and composition, could have a major impact on the diversity and food preferences of a vulnerable leaf-eating monkey (Presbytis fredericae). In response to changes in a new floristic structure, P. fredericae may develop new foraging adaptations, allowing them to diversify their diet by consuming a variety of plant species. However, such behavior may not be performed, as the monkey's food choices are evidence of an evolutionary strategy to maximize nutrient and energy intake for survival. Therefore, dietary diversity can serve as a good proxy to examine the extent to which folivore monkeys' foraging behavior adapts to food resource change. This study investigated the food diversity of plants selected by P. fredericae in a degraded montane forest on Mount Merbabu, Indonesia. We employed a molecular-based Next-Generation Sequencing (NGS) technique to analyze 13 fecal samples. Our downstream analysis in RStudio identified 132 Operational Taxonomic Units (OTUs). By organizing the OTUs by their abundance in Microsoft Excel and comparing our results to an existing floristic database from previous vegetation surveys, we identified eight orders, nine families, and nine species in the tree stratum, and 11 orders, 12 families, and 14 species in the forest floor community. These findings indicate that P. fredericae selectively consumed only 34% of the total tree species and 14% of the available forest floor plant species. This food selection suggests that P. fredericae exhibits selective feeding and optimal foraging behavior, primarily by consuming immature foliage from a wide range of plant taxa. This behavior helps them meet their nutritional needs while minimizing the risk of toxin accumulation.